Rancang Bangun Website Sistem Informasi Manajemen Rantai Pasok Distribusi Sepatu Lokal - Devinta Nurul Fitriana; Niken Ayu Setifani; Yusuf Amrozi (ULTIMA InfoSys, 2020)
Micro, small and medium enterprises (UMKM) in Indonesia is increasing every year. The increase in the number of UMKM has a significant impact on the Indonesian economy, so the government lowers the UMKM tax so that UMKM businesses develop rapidly. However, that does not make the other problems faced by the UMKM to be overcome. One problem that arises is the marketing and distribution of product results. The purpose of this research is to build a local shoe product distribution system based on a website to make it easier for resellers or shops to order shoes to the production. Processed data include retailer and store data, distributor data, product data, transaction data, and ordering data. Using the waterfall development model and using the Unified Modeling Language (UML) to visualize system modeling. This research generates reports of every activity carried out in the system including reports for factories, distributors and retailers.